Learning Each Other's Language and Building Trust: Community-Engaged Transdisciplinary Team Building for Research on Human Trafficking Operations and Disruption. (11th May 2022) - Martin, Lauren; Gupta, Mahima; Maass, Kayse L.; Melander, Christina; Singerhouse, Emily; Barrick, Kelle; Samad, Tariq; Sharkey, Thomas C.; Ayler, Tonique; Forliti, Teresa; Friedman, Joy; Nelson, Christine; et al.
Background: Human trafficking for sexual exploitation (referred to as sex trafficking) is a complex global challenge that causes harm and violates human rights. Most research has focused on victim-level harms and experiences, with limited understanding of the networks and business functions of trafficking operations. Empirical evidence is lacking on how to disrupt trafficking operations because it is difficult to study; it is hidden and dangerous, spans academic disciplinary boundaries, and necessitates ways of knowing that include lived experience. Collaborative approaches are needed, but there is limited research on methods to best build transdisciplinary teams. Aim: The aim of this study was to understand how to form a community-engaged transdisciplinary research team that combines qualitative and operations research with a survivor-centered advisory group. Methods: We conducted a qualitative meta-study of our team that is seeking to mathematically model sex trafficking operations. Data were collected from the minutes of 16 team meetings and a survey of 13 team members. Results: Analysis of meeting minutes surfaced four themes related to content and style of communication, one related to value statements, and one capturing intentional team building efforts. Survey results highlighted respect, trust, integrity, openness and asking and answering questions as key aspects of team building. Results show that an action research approach to team building, focused on trust and communication, fostered effective collaboration among social scientists, operations researchers, and survivors of trafficking. Conclusion: Team building, shared language, and trust are essential, yet often neglected, elements of team science. This meta-study provides important methodological insights on community engaged transdisciplinary team formation to tackle vexing social challenges.